Studi Literatur: Akulturasi Rasa Sebagai Metode Pengenalan Bahan Pangan Lokal Bagi Masyarakat - Ghaniyyah (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Local food is one of the country's riches. It is our obligation as Indonesian people to preserve local food. Among the onslaught of the globalization era, Indonesia's wealth is eroding because people tend to be more familiar with foreign culture, which is also foreign wealth. One of them is in the culinary field. People tend to like foreign culinary more often and more, because foreign culinary is considered cooler and more modern. Traditional Indonesian culinary delights made from local food are also under threat, which results in the threat of local Indonesian food as well. One solution to preserve local food ingredients is to acculturate flavors by combining foreign culinary delights with local food ingredients. This literature study discusses problems and solutions regarding the sustainability of local food, with the aim of enabling society to be more innovative in developing local food.